International Comparisons of Economic Burden of EndStage Renal Disease to the National Healthcare Systems - H, Ismail; MR, Abdul Manaf; AH, Abdul Gafor; ZM, Mohamad Zaher; AI, Nur Ibrahim (IIUM Medical Journal Malaysia, 2019)
The global prevalence of chronic kidney disease (CKD) is between 11 to 13%. Renal replacement therapies (RRT) – which include dialysis and renal transplantation – consume a significant portion of a country’s health resources even though only 0.1% of all CKD patients are at stage 5, also known as end-stage renal disease (ESRD). The aim of this review was to compare the magnitude of the economic burden of ESRD on national healthcare systems of selected countries with high prevalence of ESRD including Malaysia. The quantity of interest in this review were total ESRD expenditures and its proportions to the national health systems' expenditure. It was identified that total ESRD expenditure contributes between 0.91% to 7.1% of national health system expenditure in countries selected for this review. In Malaysia, the public sector - through its various agencies at the federal and state levels, accounted for almost 70% of dialysis funding; the remaining 30% came from the private sector and out-of-pocket payments. The ESRD expenditures in Malaysia constitutes 4.2% of total health expenditure by the public sector, relatively high compared to other countries. This review will summarise findings of the currently available economic evaluations of RRT in Malaysia. Based on available evidence, estimated weighted cost of treating ESRD patient in Malaysia is MYR39,346 per patient per year (USD26,648, PPP 2016).